Literature Learning in the Merdeka Belajar Curriculum in Elementary Schools: Challenges and Solutions - Suryadi, Tatang; Sunendar, Dadang; Muryanto, Rusdiono (International Conference on Elementary Education, 2025)
The Merdeka Belajar Curriculum, introduced in Indonesia in 2022, aims to offer flexible and student-centered learning that encourages creativity and independence. This study examines the implementation of literature learning in elementary schools within this framework, focusing on preparation, implementation, and evaluation stages. Despite the curriculum's potential, challenges such as inadequate teaching materials, conventional methods, and insufficient formative assessment hinder effective literature learning. Through qualitative methods including observations, interviews, and documentation at a public elementary school in Sumedang Regency, this research identifies key obstacles and suggests improvements. Proposed solutions include developing creative teaching materials tailored to students' needs, incorporating diverse and modern learning media, and employing interactive teaching methods. Regular formative assessments with constructive feedback, teacher training on effective literature teaching strategies, and collaboration with libraries and literature communities are also recommended. These solutions aim to create a more dynamic and effective literature learning environment, ultimately improving the quality of literature education in elementary schools.